Long-Term Trajectories of Posttraumatic Stress Disorder: Categorical versus Continuous Assessment. Issue 4 (2nd October 2018) - Solomon, Zahava; Bachem, Rahel; Levin, Yafit; Crompton, Laura; Ginzburg, Karni
Abstract : Objective : Long-term trajectories of posttraumatic stress disorder (PTSD) may fluctuate over time and typically conform to four heterogeneous patterns: resilience, recovery, delayed-onset, and chronic symptomatology. However, such fluctuations are typically short ranged and have rarely been investigated over the course of decades after the trauma. Moreover, existing studies have used a variety of measurements, either employing a categorical Diagnostic and Statistical Manual of Mental Disorders ( DSM )-oriented approach or a continuous measure of symptom severity. The aim of this study was to evaluate the two methods of analyzing trajectories of PTSD by examining the level of concordance between them, their sensitivity, and their validity. Method : A total of 349 Israeli veterans from the 1973 Yom Kippur War were examined at four time points over more than four decades since the war. A latent class growth analysis (LCGA) was conducted to identify different PTSD trajectories, using both categorical and continuous PTSD assessments. Results : Descriptive results revealed that the four commonly observed patterns of PTSD are insufficient for capturing the range of individual PTSD trajectories. Using a categorical measure in the explorative LCGA yielded three trajectories (resilient, chronic, and delayed onset). The continuous measure yielded five trajectories (resilient, chronic, recovered, and two delayed-onset trajectories), which provided a slightly more nuanced distinction of participants' distress-induced psychosocial dysfunction as compared to the three-trajectory solution. Conclusion : These findings suggest that using a continuous PTSD trajectory measure provides a somewhat more sensitive estimation of PTSD trajectories. More specifically, taking into consideration symptom intensity and fluctuation over time may provide a more comprehensive picture of the survivors' distress.